High birefringence bistolane liquid crystals: synthesis and properties. Issue 1 (21st December 2015) - Węgłowska, Dorota; Kula, Przemysław; Herman, Jakub
Abstract : Twenty both symmetrical and non-symmetrical bistolanes with terminal alkyl, alkoxy and alkylsulfanyl chain and lateral methyl or ethyl group have been synthesized via Sonogashira cross-coupling and their mesomorphic properties have been studied. Abstract : Twenty liquid crystals both symmetrical and non-symmetrical bistolanes with terminal alkyl, alkoxy and alkylsulfanyl chain and lateral methyl or ethyl group have been synthesized via Sonogashira cross-coupling and their mesomorphic properties have been studied. Most compounds exhibit an enantiotropic nematic phase in a broad temperature range (>40 °C). Optical properties of selected compounds have been investigated. They exhibit a high value of birefringence (>0.4).